Method for manufacturing molds with excellent collapsibility

JP7943826B2Active Publication Date: 2026-10-30ASAHI YUKIZAI KOGYO CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023010759
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-01-27
Publication Date
2026-10-30
Estimated Expiration
2042-03-30

AI Technical Summary

Benefits of technology

【0024】 このように、本発明に従うレジンコーテッドサンドにあっては、耐火性骨材として、SiO2含有量が50質量%以上である、特にケイ砂を主体とする天然骨材が用いられ、その充填率が53%以上のものであることに加えて、0.30W/m·K以上の高い熱伝導率を有すると共に、沸点が300℃以下であり且つ分子量が100以下である気化成分を300~2000ppmの割合で含むレジンコーテッドサンドとして、構成されているところから、そのようなレジンコーテッドサンドを用いて造型される鋳型の熱伝導特性が、より一層有利に高められ得ることとなるのであり、これによって、造型して得られる鋳型の内部まで効果的に硬化せしめ得て、未硬化部位の存在が有利に抑制乃至は解消され得ることとなるところから、鋳造に際して、金属溶湯の熱を鋳型全体により均一に伝え易くなるのであり、そのために、そのような金属溶湯の熱にて、耐火性骨材を結合する樹脂粘結剤の結合力を有利に低下せしめ得ることによって、鋳型の崩壊性が効果的に向上せしめられ得ることとなるのである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007943826000009
    Figure 0007943826000009
  • Figure 0007943826000010
    Figure 0007943826000010
  • Figure 0007943826000001
    Figure 0007943826000001
Patent Text Reader

Abstract

To provide a resin coated sand (RCS) capable of practically advantageously forming a mold further made higher in mold collapsibility after casting while improving mold property.SOLUTION: The RCS prepared by mixing a fire-resistant aggregate with a resin binder and covering the surface of the fire-resistant aggregate with the resin binder is configured such that the fire-resistant aggregate contains SiO2 of 50% or higher by mass, contains a vaporized component having a filling rate of 53% or higher, a boiling point of 300°C or lower, and a molecular weight of 100 or less at a rate of 300-2000 ppm, and further has a thermal conductivity of 0.30 W / m K.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to resin-coated sand with excellent mold collapsibility, and particularly relates to resin-coated sand that can advantageously form a mold with improved mold properties and excellent collapsibility after casting.

Background Art

[0002] In the production of castings by conventional sand mold casting, molten metal is cooled, solidified and hardened in a mold obtained by molding using molding sand composed of various refractory aggregates, and then the main mold and sand core constituting the mold need to be removed. As a method for removing such a mold, especially a sand core, generally, after the casting is cooled until the temperature of the casting is near normal temperature, a vibrator such as a knockout machine is used to apply vibration to the casting to collapse the sand core, thereby removing the sand core. However, since a resin such as phenolic resin is used in the sand core as a binder for bonding the molding sand to each other, the molding sand is fixed by such resin, and there are problems such as not being easily collapsed only by applying vibration, and it taking time to remove the molding sand from the casting.

[0003] Incidentally, in order to disintegrate sand cores fixed with such resin, one possible method is to use heat to thermally decompose the resin. However, in order to thermally decompose the resin contained in the sand core, it is necessary to apply a sufficient amount of heat to the sand core. For example, in the case of aluminum alloy castings, by holding the material at a temperature close to the melting point of the aluminum alloy for 1 to 2 hours, the resin can be thermally decomposed, and the solidified casting sand that forms the sand core can be broken down and separated. After such heating, the material is cooled for 5 to 6 hours, and then vibration is applied to disintegrate the sand core and remove the casting sand. However, this method has the problem that it requires a large amount of thermal energy and a long processing time for the decomposition of the resin. If any undecomposed resin remains, the energy will be absorbed even if vibration is applied, and it will not work effectively to disintegrate the sand. Therefore, sufficient heat treatment was necessary to remove the sand core.

[0004] Furthermore, Japanese Patent Publication No. 9-182952 and others propose a method of removing sand cores from inside a casting by pulverizing them by spraying high-pressure water into the interior of the casting. However, when using high-pressure water, the water splashes out, flooding the work site, which necessitates waterproofing measures for the work site and workers, thus worsening work efficiency. In addition to equipment problems such as the need to prepare a device to spray high-pressure water, the removed sand becomes wet, and there is an inherent problem that requires time-consuming work such as drying the sand in order to reuse it.

[0005] Furthermore, Japanese Patent Publication No. 9-1285 proposes a mold material for shell molds that contains, along with foundry sand and a phenolic resin, a disintegration-improving agent consisting of a zinc oxide-based compound such as ZnO or ZnO·B2O3 as an essential component. It is revealed that by further combining such zinc oxide-based compounds with Br-containing organic compounds or halogen-containing compounds such as ZnBr2, the sand removal process after casting becomes even easier. However, the use of such halogen-based additives presents a problem in that, although the mold disintegration is good, it causes corrosion of the casting and the casting mold, making it difficult to adopt in practical use.

[0006] In addition, Japanese Patent Publication No. 62-124046 and Japanese Patent Publication No. 5-79423 have revealed that by including alkali metal salts of aromatic carboxylic acids or thermal decomposition products of alkali metal salts or alkaline earth metal salts of permanganate as disintegration enhancers in the mold material for shell molds, the disintegration properties and sand removal properties of the mold after casting can be improved. However, there are limits to the improvement in mold disintegration properties by adding these disintegration enhancers, and increasing the amount of such disintegration enhancers used in order to further enhance the disintegration properties of the mold has inherent problems such as adverse effects on the physical properties of the mold.

[0007] Thus, every known method for improving the collapse properties of a mold has its own inherent problems, and none of them can be directly adopted in practical terms to advantageously enhance the collapse properties of a mold after casting. [Prior art documents] [Patent Documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 9-182952 [Patent Document 2] Japanese Patent Application Publication No. 9-1285 [Patent Document 3] Japanese Patent Application Publication No. 62-124046 [Patent Document 4] Special Publication No. 5-79423 [Overview of the project] [Problems that the invention aims to solve]

[0009] Herein, the present invention has been made against the background of the above circumstances, and its objective is to provide a resin-coated sand with excellent mold collapse properties, and another objective is to provide a resin-coated sand that can practically advantageously create a mold that improves mold properties while further enhancing mold collapse after casting. [Means for solving the problem]

[0010] Furthermore, in order to solve the above-mentioned problems, the present invention can be suitably implemented in various embodiments as listed below, and each embodiment described below can be adopted in any combination. It should be noted that the embodiments or technical features of the present invention are not limited in any way to those described below, and should be understood based on the inventive concept grasped from the entire specification.

[0011] First, the first aspect of the present invention is a resin-coated sand obtained by kneading a refractory aggregate and a resin binder, and coating the surface of the refractory aggregate with the resin binder, wherein the refractory aggregate contains 50% by mass or more of SiO2, has a filling rate of 53% or more, contains vaporized components with a boiling point of 300°C or less and a molecular weight of 100 or less in a ratio of 300 to 2000 ppm, and further has a thermal conductivity of 0.30 W / m·K or more, and is characterized by being a resin-coated sand with excellent mold collapse properties.

[0012] Furthermore, a second aspect of the present invention is characterized in that the fire-resistant aggregate mainly consists of silica sand and / or SiO2-based artificial aggregate.

[0013] Furthermore, a third aspect of the present invention is characterized in that the refractory aggregate has an AFS index of 30 to 90.

[0014] In addition, a fourth feature of the present invention is characterized in that the resin binder contains a phenolic resin as a main component.

[0015] And a fifth feature according to the present invention is characterized in that it is a dry resin-coated sand having free flowability at normal temperature.

[0016] Further, a sixth feature of the present invention is characterized in that the vaporizable component is liquid at 50°C.

[0017] Furthermore, a seventh feature according to the present invention is characterized in that the vaporizable component contains at least one selected from the group consisting of water, methanol and phenol.

[0018] In addition, an eighth aspect of the present invention is characterized in that a water retaining agent is further incorporated.

[0019] Further, a ninth aspect according to the present invention is characterized in that a collapsibility improving agent is further incorporated.

[0020] Furthermore, a tenth aspect of the present invention is characterized in that a good thermal conductor is further incorporated.

[0021] In addition, an eleventh aspect according to the present invention is characterized in that at least a part of the refractory aggregate is constituted of refractory particles having a shape factor of 1.40 or less, a surface-adhered clay content of 0.20 mass% or less, and further a hydrochloric acid-soluble content of 3 mass% or less.

[0022] Further, a twelfth aspect according to the present invention is characterized in that the refractory particles are regenerated from recovered sand recovered in a casting process.

[0023] Further, the thirteenth aspect of the present invention is characterized by being used for molding a mold for casting an aluminum alloy molten metal.

Effects of the Invention

[0024] As described above, in the resin coated sand according to the present invention, as the refractory aggregate, a natural aggregate mainly composed of silica sand having an SiO₂ content of 50 mass% or more is used, which has a filling rate of 53% or more, and also has a high thermal conductivity of 0.30 W / m·K or more, and is configured as a resin coated sand containing a vaporizable component having a boiling point of 300°C or lower and a molecular weight of 100 or less at a ratio of 300 to 2000 ppm. Thereby, the thermal conductivity property of the mold molded using such a resin coated sand can be further advantageously enhanced, the interior of the obtained molded mold can be effectively cured, and the presence of uncured portions can be advantageously suppressed or eliminated. During casting, the heat of the molten metal is more easily and uniformly transferred to the entire mold, so that the heat of such molten metal can advantageously reduce the bonding force of the resin binder that binds the refractory aggregate, and thus the collapsibility of the mold can be effectively improved.

[0025] Moreover, in the mold obtained by molding using such a resin coated sand according to the present invention, since the resin coated sand has excellent thermal conductivity, the presence of uncured portions that cannot be sufficiently cured even by heating during molding as in the prior art can be effectively reduced or eliminated. As a result, improvement of mold properties such as strength can be advantageously realized, the molding cycle time can also be effectively shortened, and further, the amount of gas generated from the mold during casting can be effectively reduced, so that suppression or prevention of the occurrence of casting defects can also be advantageously realized.

Brief Description of the Drawings

[0026] [Figure 1]This is a cross-sectional diagram illustrating the vertical section of the casting test sand mold used to measure the core's collapse properties in the example. [Figure 2] This is a cross-sectional diagram illustrating the vertical section of an aluminum alloy casting containing a waste core in the example. [Modes for carrying out the invention]

[0027] Incidentally, resin-coated sand (RCS) according to the present invention is obtained by kneading refractory aggregate and a resin binder, and coating the surface of the refractory aggregate with the resin binder. In this case, as the refractory aggregate constituting such RCS, natural or artificial refractory particles mainly composed of silica sand, in particular natural particles (aggregate) are advantageously used to improve the thermal conductivity of the RCS. In this case, in addition to using only silica sand (including silica ore that has been crushed and sieved; the same applies hereinafter), there is no problem with using mixed sand which is a mixture of silica sand and various known foundry sands. Furthermore, recovered sand and recycled sand, in particular refractory particles recycled from recovered sand recovered in the casting process, can also be used together with new sand, or in place of new sand. However, it is desirable that the refractory aggregate, which consists of such refractory particles, generally contains 50% by mass or more of SiO2, and more preferably 60% by mass or more, and even more preferably 70% by mass or more of SiO2, as this can contribute even more favorably to improving the thermal conductivity of the RCS.

[0028] In this invention, the refractory particles used have a packing density of 53% or more. Such refractory particles with a packing density can be obtained by removing small particles, rounding the edges of the particles by polishing, spheroidizing them, or adjusting the particle size. If refractory particles with a packing density lower than this are used, it becomes difficult to obtain RCS with good thermal conductivity, and therefore it becomes difficult to improve the collapse resistance of molds formed using such RCS.

[0029] The packing ratio mentioned above refers to the ratio of the volume of the sand particles filling the apparent volume of the foundry sand. In this invention, such a packing ratio is defined as a value measured by the following method. First, 100 ml of a mixed solution of water and methanol in a weight ratio is placed in a 200 ml graduated cylinder. Then, 100 ml of foundry sand (refractory particles), measured by pouring using another graduated cylinder, is gradually added. After sealing the cylinder and confirming that no more bubbles have appeared, the liquid level in the graduated cylinder is read. The difference between this value (M ml) and the 200 ml mark (200-M) is determined as the void ratio (V). Furthermore, the value obtained by subtracting this void ratio (V) from 100 (100-V) is determined as the packing ratio (X). It should be noted that instead of a mixture of water and methanol, a mixture of water and a surfactant, or other liquids, can be used as the liquid contained in the graduated cylinder.

[0030] Furthermore, in the present invention, refractory particles having a shape factor of 1.40 or less are preferably used. Here, the shape factor of the refractory particles (aggregate) used in the present invention is also called the particle shape factor or particle shape index, and is generally used as a measure of the external shape of the particles. The closer the value is to 1, the closer it is to a spherical shape (perfect sphere). Such a shape factor can be measured by various known methods. For example, as clearly shown in Japanese Patent Publication No. 3253579, one method involves measuring the surface area of ​​actual sand grains per gram using a sand surface area meter (manufactured by George Fischer), and then dividing that value by the theoretical surface area, which is the surface area assuming all sand grains are spherical, to obtain the shape factor.

[0031] Furthermore, refractory particles with a shape factor of 1.40 or less can be obtained by, for example, removing small particles, rounding the corners of particles by polishing, spheroidizing them, or adjusting the particle size, similar to how a filling rate of 53% or more is achieved. However, if this shape factor exceeds 1.40, problems arise such as difficulty in increasing the filling rate, making it difficult to obtain RCS with good thermal conductivity. Consequently, it becomes difficult to adequately contribute to improving the collapse resistance of molds formed using such RCS.

[0032] Furthermore, in the present invention, when the refractory aggregate is recycled sand obtained by recycling recovered sand recovered in the casting process, it is desirable that the clay content adhering to the aggregate surface is 0.20% by mass or less, and that the hydrochloric acid-soluble content in the aggregate is adjusted to 3% by mass or less. The clay content adhering to the surface of such refractory aggregate can be removed by ordinary polishing, and hydrochloric acid-soluble components in the refractory aggregate, such as non-magnetic metal components, can be separated and removed from the refractory aggregate, which is a non-magnetic inorganic particle, by sieving or sorting using a conventionally known eddy current separator. Conversely, if the content of clay and hydrochloric acid-soluble components exceeds the above-specified values, it becomes difficult to sufficiently improve the packing rate and thermal conductivity of the refractory aggregate, and the objectives of the present invention become difficult to achieve advantageously.

[0033] Furthermore, refractory aggregates whose characteristics such as filling density have been adjusted in this manner have excellent thermal conductivity, and in particular, by providing aggregate particles with a thermal conductivity of 0.22 W / m·K or higher, and further by preparing them to contain 20% or more by mass of such aggregate particles, it is possible to advantageously provide RCS with excellent thermal conductivity, thereby advantageously improving the collapse properties of molds formed using such RCS.

[0034] Furthermore, it is desirable that the refractory particles (refractory aggregates) described above have an AFS index of 30 to 90, preferably 35 to 80, and more preferably 40 to 70. If the AFS index is less than 30, the particle size of the refractory particles becomes too large, which negatively affects the thermal conductivity and may reduce the properties of the mold, as well as causing problems such as deterioration of the casting surface. On the other hand, if the AFS index exceeds 90, the particle size of the refractory particles becomes too small, which can lead to problems such as the formation of clumps (aggregates of refractory particles) when mixed with the resin binder, and difficulty in sufficiently improving the thermal conductivity.

[0035] The RCS according to the present invention is formed by kneading a predetermined resin binder into the above-mentioned refractory aggregate and coating the surface of the refractory aggregate with the resin binder. Various conventionally known resin binders can be used, such as phenolic resin, furan resin, urethane resin, amine polyol resin, unsaturated polyester resin, diallyl phthalate resin, polyether polyol resin, etc., and can be appropriately selected from these. In the present invention, however, phenolic resin is advantageously used.

[0036] Incidentally, in the present invention, the phenolic resin suitably used as a resin binder is, as is well known, a solid or liquid (including varnish or emulsion forms) condensation product obtained by reacting phenols and aldehydes in the presence of an acidic or basic catalyst, and is referred to as a novolac type or resol type depending on the type of catalyst used, and is a phenolic resin that exhibits thermosetting properties by heating in or without a predetermined curing agent or curing catalyst.

[0037] Furthermore, the phenols used as raw materials for such phenolic resins refer to phenols and phenol derivatives, and examples include known phenols such as cresol, xylenol, p-tert-butylphenol, nonylphenol and other alkylphenols, resorcinol, bisphenol F and bisphenol A and other polyhydric phenols, naphthols, and mixtures thereof. One of these may be used alone or in combination of two or more.

[0038] Furthermore, examples of aldehydes include formalin, which is an aqueous solution of formaldehyde, as well as paraformaldehyde, trioxane, acetaldehyde, paraaldehyde, propionaldehyde, and others. Other known aldehyde compounds can also be used as appropriate. These aldehydes can be used individually or in combination of two or more, without any difference.

[0039] In this invention, the novolac-type phenolic resin is formed by condensing the above-mentioned phenols and aldehydes with an acidic catalyst, such as an inorganic acid like hydrochloric acid, sulfuric acid, or phosphoric acid, or an organic acid like oxalic acid, p-toluenesulfonic acid, benzenesulfonic acid, or xylenesulfonic acid, or an acidic substance like zinc oxide, zinc chloride, magnesium oxide, or zinc acetate, as is well known. The molar ratio (F / P) of aldehydes (F) to phenols (P) is appropriately selected depending on the type of reaction catalyst used, but is preferably selected within the range of 0.55 to 0.80.

[0040] On the other hand, resol-type phenolic resins are formed by condensing the above-mentioned phenols and aldehydes using a known basic catalyst, in the same manner as in the conventional method. As the basic catalyst, alkali metal or alkaline earth metal hydroxides such as sodium hydroxide and calcium hydroxide, or alkaline earth metal oxides can be used, as well as amines such as dimethylamine, triethylamine, butylamine, dimethylbenzylamine, and naphthalenediamine, ammonia, hexamethylenetetramine, and other divalent metal naphthenates or divalent metal hydroxides can be used. Furthermore, the molar ratio (F / P) of aldehydes to phenols in such a condensation reaction is appropriately selected depending on the type of reaction catalyst used, but is generally selected within the range of 1.1 to 4.0.

[0041] Furthermore, the novolac-type phenolic resins and resol-type phenolic resins mentioned above can be used individually or mixed in appropriate proportions without any problem. In addition, as is well known, modified phenolic resins obtained by changing some of the phenol to components such as bisphenol A and naphthol can also be used, and they can even be used as benzylic ether-type phenolic resins.

[0042] Furthermore, when mixing a resin binder such as the phenolic resin mentioned above into the refractory aggregate, the amount of such resin binder to be added is determined appropriately considering the type of resin used, the required strength of the mold, etc., and cannot be uniquely defined. However, generally, it is in the range of 0.2 to 10 parts by mass per 100 parts by mass of the refractory aggregate, preferably in the range of 0.5 to 8 parts by mass, and more preferably in the range of 1 to 5 parts by mass.

[0043] Thus, the RCS obtained by kneading refractory aggregate and a resin binder, and coating the surface of the refractory aggregate with the resin binder, contains 300 to 2000 ppm of vaporizable components with a boiling point of 300°C or less and a molecular weight of 100 or less, so that it can vaporize at 300°C or less, and is further configured to have a thermal conductivity of 0.30 W / m·K or higher. This effectively enhances the post-cast collapse properties of molds obtained by molding from such RCS. However, if the content of such vaporizable components is less than 300 ppm, or if the thermal conductivity is lower than 0.30 W / m·K, there is a problem in that the mold collapse properties cannot be fully exhibited. Furthermore, if the content of vaporizable components is more than 2000 ppm, blocking of the RCS is more likely to occur during mold molding, causing problems such as difficulty in molding the desired mold.

[0044] Therefore, the RCS according to the present invention is advantageously prepared as a dry RCS that has free flow at room temperature, and when its dynamic angle of repose is measured, a measurement of the dynamic angle of repose can be obtained. Here, the dynamic angle of repose is measured by placing the RCS in a cylinder having one end face transparent and flat (for example, filling a container with a diameter of 7.2 cm and a height of 10 cm with RCS up to half its volume), rotating it around an axis at a constant speed (for example, 25 rpm), and measuring the angle formed between the slope and the horizontal plane when the slope of the coated sand layer flowing in the cylinder becomes planar. The dynamic angle of repose for such a dry RCS is preferably 80° or less, more preferably 45° or less, and even more preferably 30° or less. In particular, when the refractory aggregate is spherical, a dry RCS having a dynamic angle of repose of 45° or less can be easily realized. In contrast, when RCS is in a moist state, does not flow within the cylinder, and the slope of the RCS layer does not form a plane, and therefore the dynamic angle of repose cannot be measured, it is considered to be a wet RCS.

[0045] Furthermore, in accordance with the present invention as described above, the vaporized component contained in the RCS functions as a heat transfer medium, and such a vaporized component is appropriately selected from various known substances having a boiling point of 300°C or less and a molecular weight of 100 or less. Specifically, hydrocarbons such as cyclohexane, toluene, hexane, and benzene; alcohols such as ethanol, n-butanol, t-butanol, furfuryl alcohol, and methanol; ethers and acetals such as 1,4-dioxane, tetrahydrofuran, trioxane, and furfural; ketones such as acetone, methyl ethyl ketone, diethyl ketone, and cyclohexanone; ethyl acetate, methyl acetate, and γ-butyl The following substances will be appropriately selected from among esters such as loractone; polyhydric alcohols and their derivatives such as ethylene carbonate, ethylene glycol, ethylene glycol dimethyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, glycerin, trimethylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, and propylene glycol; carboxylic acids such as lactic acid, propionic acid, butyric acid, and maleic anhydride; phenols such as phenol; nitrogen-containing compounds such as acetamide, acetonitrile, aniline, imidazole, and diethylamine; and liquid substances such as water. In particular, in the present invention, at least one of water, methanol, and phenol will be advantageously included as a vapor component.

[0046] Furthermore, if the molecular weight of the vaporized component exceeds 100, it becomes difficult for the component to volatilize and penetrate into the interior and corners of the mold, resulting in a reduced ability to improve internal hardening. Additionally, if its boiling point is higher than 300°C, it becomes difficult to volatilize sufficiently, hindering diffusion within the mold and making it difficult to fully enjoy the effects of the present invention. Moreover, if the boiling point of the vaporized component is too low, there is a risk that the vaporized component may escape from the RCS before mold formation. Therefore, it is generally desirable for the vaporized component to have a boiling point higher than 50°C. Accordingly, as the vaporized component used in the present invention, it is advantageous to use one that is liquid at 50°C.

[0047] Incidentally, in the RCS targeted by the present invention, water or moisture, which is the vaporized component mentioned above, is inevitably introduced as a component or solvent component of the resin binder used in its formation, and as an additive such as a curing agent which may be added as needed, and thus constitutes one of the components of the RCS. In the manufacturing process of the RCS, a water-retaining agent is suitably added to the RCS so that such water or moisture-containing vaporized components can be favorably retained in the RCS and the amount of vaporized components in the RCS can be favorably secured within the range defined in the present invention.

[0048] The amount of water-retaining agent used is generally preferably 0.5 to 50 parts by mass, more preferably 1 to 40 parts by mass, and especially preferably 2 to 30 parts by mass, per 100 parts by mass of resin (solids) in the resin binder that provides the coating layer formed on the surface of the refractory aggregate in the RCS. If the amount of water-retaining agent is too small, it may be difficult to enjoy its beneficial effects. On the other hand, if the amount is too large, blocking due to moisture absorption may occur, and the improvement in effect in proportion to the amount used may not be observed, which is not advisable from the standpoint of cost-effectiveness. The water-retaining agent used here is also recognized as a humectant and can be appropriately selected from known substances such as polyhydric alcohols, water-soluble polymers, hydrocarbons, sugars, proteins, and inorganic compounds.

[0049] Specifically, examples of polyhydric alcohols that are one type of water-retaining agent include diethylene glycol, triethylene glycol, polyethylene glycol, dipropylene glycol, polypropylene glycol, pentanediol, hexanediol, 2-ethyl-1,3-hexanediol, heptanediol, octanediol, hexanetriol, thioglycol, hexylene glycol, and trimethylolpropane. Examples of water-soluble polymer compounds include polyvinyl alcohol and its various modified products; liquid resol resins such as alkali resol resins; superabsorbent polymers such as sodium polyacrylate; cellulose derivatives such as alkylcellulose, hydroxyalkylcellulose, alkylhydroxyalkylcellulose, carboxymethylcellulose, hydroxyethylcellulose, and hydroxypropylmethylcellulose; and starch derivatives such as alkyl starch, carboxymethyl starch, and oxidized starch. Furthermore, examples of hydrocarbons include aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, petroleum ethers, petroleum benzyl, tetralin, decalin, tert-amylbenzene, and dimethylnaphthalene. Furthermore, examples of sugars include monosaccharides, oligosaccharides, and polysaccharides such as dextrin, and examples of proteins include gelatin. In addition, examples of inorganic compounds include sodium chloride, sodium sulfate, calcium chloride, magnesium chloride, and silicates. These various water-retaining agents can be used individually or in combination of two or more.

[0050] Furthermore, according to another preferred embodiment of the present invention, the RCS according to the present invention further contains, together with or in lieu of the above-mentioned water-retaining agent, at least one of the following as a disintegration enhancer: an oxyacid salt, a phosphate ester, an aliphatic condensed phosphate ester, an organic carboxylate metal salt, and a carbonate compound. This effectively improves the disintegration properties of the mold formed using such an RCS. The oxyacid salt used here is generally preferably an alkali metal oxyacid salt, specifically, an alkali metal nitrate salt, an alkali metal permanganate salt, an alkali metal molybdate salt, an alkali metal tungstate salt, etc. Among these, from the standpoint of mold strength, an alkali metal nitrate salt, an alkali metal molybdate salt, and an alkali metal tungstate salt are preferred, and moreover, an alkali metal nitric acid salt, such as potassium nitrate and sodium nitrate, is particularly preferred. The content of such an oxyacid salt is generally about 0.1 to 50 parts by mass, preferably about 1 to 20 parts by mass, per 100 parts by mass of the resin binder.

[0051] Furthermore, examples of the phosphate esters and aliphatic condensed phosphate esters used as disintegration enhancers include various aliphatic and aromatic phosphate esters such as trimethyl phosphate, triethyl phosphate, tributyl phosphate, tri-2-ethylhexyl phosphate, tributoxyethyl phosphate, triphenyl phosphate, diethyl-N,N-bis(2-hydroxyethyl)aminomethylphosphonate, and dibutyl butylphosphonate, as well as aliphatic condensed phosphate esters such as Fyrol PNX (manufactured by ICL JAPAN Co., Ltd.). These will be appropriately selected and used. Generally, the content of these phosphate esters and / or aliphatic condensed phosphate esters is 0.5 to 30 parts by mass, more preferably 1 to 10 parts by mass, per 100 parts by mass of the resin binder.

[0052] Furthermore, the above-mentioned organic carboxylic acid metal salts are salts of an organic carboxylic acid and a metal. Examples of organic carboxylic acids that constitute such organic carboxylic acid metal salts include fatty acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, and elaidic acid; cyclohexanecarboxylic acid, phenylacetic acid, benzoic acid, o-toluic acid, m-toluic acid, p-toluic acid, o-chlorobenzoic acid, m-chlorobenzoic acid, p-chlorobenzoic acid, o-bromobenzoic acid, m-bromobenzoic acid, and p-bromobenzoic acid. Examples of aromatic carboxylic acids include o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, salicylic acid, p-hydroxybenzoic acid, o-aminobenzoic acid, m-aminobenzoic acid, p-aminobenzoic acid, o-methoxybenzoic acid, m-methoxybenzoic acid, and p-methoxybenzoic acid; saturated dibasic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, superiic acid, azelaic acid, sebacic acid, and tartaric acid; and aromatic dibasic acids such as phthalic acid, isophthalic acid, and terephthalic acid.

[0053] On the other hand, examples of metals that constitute the above-mentioned organic carboxylate metal salt include lithium, sodium, magnesium, aluminum, potassium, calcium, titanium, manganese, iron, nickel, copper, zinc, barium, and tin. In the dibasic acid, at least one carboxyl group is salted with the above-mentioned metal. The amount of this organic carboxylate metal salt is preferably set in the range of 0.1 to 15 parts by mass per 100 parts by mass of phenolic resin. This amount varies depending on the performance required for the mold, but generally, if the amount of organic carboxylate metal salt is less than 0.1 parts by mass, the mold tends to become uncollapsible, and conversely, if it exceeds 15 parts by mass, the strength of the binder decreases, and the handling of the mold tends to worsen.

[0054] In addition, carbonate compounds selected from the group consisting of metal carbonate salts, metal bicarbonate salts, and metal percarbonate salts can also be used as disintegration enhancers. Examples of metal carbonate salts include potassium carbonate, sodium carbonate, lithium carbonate, calcium carbonate, magnesium carbonate, barium carbonate, zinc carbonate, lead carbonate, copper carbonate, and aluminum carbonate. Examples of metal bicarbonate salts include potassium bicarbonate, sodium bicarbonate, and lithium bicarbonate. Examples of metal percarbonate salts include potassium percarbonate, sodium percarbonate, and lithium percarbonate. In the present invention, particularly preferred carbonate compounds include potassium carbonate, sodium carbonate, lithium carbonate, potassium bicarbonate, sodium bicarbonate, lithium bicarbonate, potassium percarbonate, sodium percarbonate, and lithium percarbonate, which can be used individually or in combination.

[0055] Furthermore, according to another preferred embodiment of the present invention, the RCS according to the present invention may further contain, together with or in lieu of, the water-retaining agent and / or disintegration-improving agent described above, a good thermal conductor such as a metal oxide, metal powder, or non-oxide ceramic, thereby further improving the disintegration properties of the mold. Here, such a good thermal conductor generally exhibits a particle or powder form with an average particle diameter of 100 μm or less, and is incorporated into the RCS by being mixed during the kneading of the refractory aggregate and the resin binder. Specifically, examples of such a good thermal conductor include metal oxides such as iron, copper, nickel, cobalt, and zinc, and include ferrous oxide, ferric oxide, iron(II,III) oxide, iron hydroxide, cobalt(III) oxide, cobalt(II) oxide, nickel(III) oxide, nickel(II) oxide, cuprous oxide, cupric oxide, zinc oxide, and the like. Furthermore, metal powders such as iron powder, aluminum powder, zinc powder, and copper powder are used, and non-oxide ceramics such as silicon carbide, silicon nitride, aluminum nitride, sialon, and carbon composite materials are used. Generally, the total content of such good thermal conductors is about 0.1 to 3 parts by mass, preferably about 0.1 to 1 part by mass, and more preferably about 0.1 to 0.5 parts by mass, per 100 parts by mass of refractory aggregate.

[0056] In addition to the above-mentioned components, various conventionally used additives may also be appropriately blended and included in the RCS as needed, for purposes such as improving the physical properties of the RCS and mold. For example, waxes such as paraffin wax, synthetic polyethylene wax, and montanic acid wax; fatty acid amides such as stearate amide, oleic acid amide, and erucic acid amide; and alkylene fatty acid amides such as methylenebisstearate amide and ethylenebisstearate amide can be included in the production of either the resin or the RCS as lubricants that contribute to improving the fluidity of the RCS. Stearic acid, stearyl alcohol, metal stearate salts, lead stearate, zinc stearate, calcium stearate, magnesium stearate, monoglyceride stearate, stearyl stearate, and hardened oils can be added during the production of the RCS. Furthermore, benzenecarboxylic acids such as benzoic acid, salicylic acid, para-aminobenzoic acid, anthranilic acid, phthalic acid, and terephthalic acid can be included as additives that contribute to improving the curing speed of the mold during the production of either the resin or the RCS. In addition, it is also effective to include coupling agents that strengthen the bond between the refractory aggregate and the resin binder; for example, silane coupling agents, zircon coupling agents, and titanium coupling agents can be included during the production of either the resin or the RCS. In addition, paraffin, wax, light oil, machine oil, spindle oil, insulating oil, waste oil, vegetable oil, fatty acid esters, organic acids, graphite fine particles, mica, vermiculite, fluorine-based release agents, and silicone-based release agents can also be used as release agents.

[0057] Incidentally, when manufacturing RCS according to the present invention using the above-mentioned compounding components, the resin binder and other compounding components are kneaded with the predetermined refractory particles (aggregate) in accordance with conventional methods. The manufacturing method used is not particularly limited, and any conventionally known method such as the dry hot coat method, semi-hot coat method, cold coat method, or powder solvent method can be employed. However, in the present invention, it is particularly recommended to employ the so-called dry hot coat method, in which the preheated refractory particles and resin binder are kneaded in a kneader such as a whirl mixer or speed mixer, an aqueous solution of a predetermined curing agent or curing accelerator such as hexamethylenetetramine, and other compounding components are added, and the lump contents are separated into granules by forced-air cooling, and then a lubricant such as calcium stearate is added. The preheating temperature for the refractory particles in the dry hot-coat method described above will be appropriately selected considering the manufacturing conditions of the RCS, etc., so that the content of vaporized components containing water in the final RCS is within the range specified in the present invention. Generally, a temperature of about 100 to 160°C, preferably about 100 to 140°C, is used. The timing for mixing additives such as resin binders and curing agents / curing accelerators with the refractory particles will be appropriately selected based on the knowledge of those skilled in the art. They can be mixed individually, sequentially, or in appropriate combinations.

[0058] The RCS obtained according to the present invention contains a predetermined vaporization component in a ratio of 300 to 2000 ppm, and when its thermal conductivity is measured in its granular form, it has a thermal conductivity of 0.30 W / m·K or higher, preferably 0.33 W / m·K or higher, unlike conventional RCS, thereby advantageously contributing to the improvement of mold collapse properties, which is the objective of the present invention. Here, the thermal conductivity of the RCS can be measured by a transient hot wire heating method (probe method) in accordance with JIS-R-2551-1:2007. Specifically, using a rapid thermal conductivity meter (QTM-710) manufactured by Kyoto Electronics Manufacturing Co., Ltd., the RCS to be measured is placed in a designated powder container, and a probe (heating wire + thermocouple) is used to heat the wire by passing a constant current through it, while the temperature of the heating wire is measured with the thermocouple. The thermal conductivity of the RCS to be measured is then determined from the slope of the resulting temperature rise graph (a graph with a logarithmic time axis).

[0059] Furthermore, it is desirable that the RCS according to the present invention, as described above, has a low content of so-called clumps, which are composite particles formed by the bonding (aggregation) of multiple refractory particles that occur during the manufacturing process. Generally, when the RCS removed from the manufacturing process is sieved, it is recommended that the amount of clumps that do not pass through a 20-mesh sieve, in other words, the amount of clumps on the 20-mesh sieve, be 3% by mass or less, more preferably 1% by mass or less, relative to the total amount of RCS. Conversely, if the amount of clumps in the RCS is large, the filling ability into the molding cavity of the mold for forming the mold deteriorates, adversely affecting the hardening characteristics of the mold, making it difficult to sufficiently improve mold characteristics such as mold strength, and causing problems such as insufficient mold collapse after casting. Furthermore, the amount of such clumps can be controlled by using refractory aggregate with a particle size index (AFS) within a preferred range related to the present invention, and by limiting the amount of good thermal conductors such as metal oxides with an average particle diameter of 100 μm or less to a preferred range.

[0060] Furthermore, when forming a predetermined mold, such as a shell mold, using the RCS obtained as described above, the mold is formed under heating in order to heat-harden the RCS. However, there are no particular limitations on the heating method used, and any conventionally known method can be used to its advantage. For example, the RCS described above can be filled into a mold preheated to about 150-300°C, which has a desired shape space to give the desired mold, by gravity drop or blowing, and after hardening, the hardened mold can be removed from the mold to obtain the desired casting mold. In particular, a mold obtained by forming it using such RCS under conditions of 250°C for 60 seconds has the characteristic of having a hardening rate of 30% or more by area ratio. Furthermore, the molded form can be subjected to a secondary firing process at a temperature of approximately 200-300°C as needed. This process can advantageously accelerate the hardening of the mold, significantly improving its ability to withstand collapse.

[0061] Furthermore, using the mold obtained through such shaping, a predetermined molten metal, such as molten aluminum alloy, is cast. After solidification, the casting is vibrated using a vibrator such as a knockout machine to collapse the mold, thereby removing it. However, in the case of a mold using RCS according to the present invention, in addition to the improvement in the hardening rate of the mold due to the heat conduction effect via the vaporized components in the RCS, the RCS itself has high thermal conductivity. As a result, the heat of the poured molten metal effectively accelerates the deterioration of the resin binder that binds the refractory aggregate, advantageously reducing the bonding strength. Consequently, the mold can be easily collapsed by applying vibration for a short time, and the removal of the mold (foundry sand) can be carried out simply and easily. [Examples]

[0062] The present invention will be further clarified by showing some embodiments below, but it goes without saying that the present invention is not limited in any way by the description of such embodiments. It should be understood that, in addition to the embodiments below and the specific descriptions above, various changes, modifications, and improvements can be made to the present invention based on the knowledge of those skilled in the art, as long as they do not depart from the spirit of the present invention.

[0063] Furthermore, in the following description, parts and % refer to parts by mass and mass%, respectively, unless otherwise specified, except that the filling rate is container percent. In addition, the characteristics of the RCS manufactured below, as well as the mold characteristics and mold collapse properties obtained therefrom, were evaluated according to the following method.

[0064] - Measuring the filling density - For each type of foundry sand, the packing density is determined according to the measurement method described earlier in the main text of this specification.

[0065] -Measurement of shape factor- For each type of foundry sand, a sand surface area meter (manufactured by George Fischer) is used to measure the actual surface area of ​​the sand grains per gram. This value is then divided by the theoretical surface area, which is the surface area assuming all sand grains are spherical, and this value is defined as the shape factor.

[0066] -Measurement of clay content- 50g of the sample sand (foundry sand) is accurately weighed to determine the weight of the sand before treatment. This weight is then placed in a 500ml glass beaker, 300ml of water is added, and then one grain of sodium hydroxide (approximately 200mg) is added. Next, the mixture is boiled on an electric heater for 30 minutes, the boiling water is discarded, the mixture is washed several times with water, and then dried in a dryer. The weight of the dried sample sand is accurately weighed to determine the weight of the sand after treatment. The clay content (%) is then calculated based on the obtained sand weights according to the following formula. Clay content (%) = [(Mass of sand before treatment) - (Mass of sand after treatment)] / (Mass of sand before processing) × 100

[0067] -Measurement of hydrochloric acid soluble content- Approximately 10 g of sample sand is accurately weighed and placed in a Kjeldahl tube. Then, 50 ml of 20% hydrochloric acid is added to the Kjeldahl tube and heated at 180°C for approximately 20 minutes. After heating, the Kjeldahl tube is cooled, its contents are filtered, thoroughly washed with tap water, and then heated and dried. The weight of the hydrochloric acid-treated sample sand is then accurately weighed. The amount of sample sand lost due to the hydrochloric acid treatment is expressed as a percentage and is defined as the hydrochloric acid-soluble content.

[0068] - Measuring moisture content (%) - The water content in RCS can be measured by the Karl Fischer method or by the weight change when heated in a dryer, but here it was determined by the following method. First, 2.0 g of the obtained RCS was placed into a flask of a Karl Fischer moisture meter (Hiranuma Sangyo Co., Ltd.: AQV-7 HIRANUMA AUQA COUNTER) containing 100 mL of the dehydrating solvent Aquamicron ML (Mitsubishi Chemical Corporation) [the Karl Fischer reagent (Sigma-Aldrich Laborchemikalien GmbH: Hydranal Composite 5) was added dropwise beforehand to make the water content 0], then stirred for several minutes using a magnetic stirrer, and then the Hydranal Composite 5 was added dropwise to quantify the water content, and the water content was calculated from the obtained value.

[0069] -Measurement of thermal conductivity- Using a rapid thermal conductivity meter (QTM-710) manufactured by Kyoto Electronics Manufacturing Co., Ltd., the thermal conductivity of each sample (RCS) is calculated from the temperature rise graph obtained according to the method described above.

[0070] -Measurement of clump content- The RCS obtained in each example is sieved through a 20-mesh sieve, and composite particles (clumps) with a particle size of 20 mesh or larger are removed from the sieve. The amount of clumps is calculated as the mass percentage of the mass of clumps relative to the mass of sand (refractory aggregate) used in mixing, according to the following formula. Amount of clumps (%) = [Mass of clumps / (Mass of clumps + Mass of sand with a mesh size of 20 or less)] × 100

[0071] -Measuring mold strength- For each RCS, test specimens measuring 10 mm wide x 10 mm thick x 60 mm long (molding temperature: 250°C, time: 60 seconds) are obtained, and further, for specimens subjected to secondary firing (250°C x 240 seconds), the fracture load of each specimen is measured using a measuring instrument (Takachiho Seiki Co., Ltd.: Digital Foundry Sand Strength Tester). Then, using these measured fracture loads, the flexural strength is calculated using the following formula and defined as the mold strength. Transverse bending strength (N / cm 2 ) = 1.5 × LW / ab 2 [However, L: distance between supports (cm), W: breaking load (N), a: width of the test specimen (cm), b: thickness of the test specimen (cm)]

[0072] -Measurement of hardening rate- A cylindrical mold with a diameter of 50 mm and a height of 50 mm is fabricated (at 250°C for 90 seconds), then cooled, and the resulting cooled mold is cut at a height of 25 mm. Next, the unhardened portion is dissolved and removed from the cut surface of the mold with acetone, then dried, and its weight is measured. This weight is then divided by the weight when fully hardened, and the resulting ratio is defined as the hardening rate.

[0073] -Evaluation of disintegration- First, as shown in Figure 1, dogbone-shaped tensile strength test specimens 2 with dimensions of width: 40 mm, length: 75 mm, and thickness: 25 mm were prepared for each RCS and used as cores for collapse tests.

[0074] Next, an outer mold 4 with dimensions of 125 mm × 80 mm × 75 mm, having a space slightly larger than the core test piece 2, was separately prepared. The core test piece 2 was then placed inside this outer mold 4, and molten aluminum alloy at a temperature of 720°C was poured in at an S / M ratio of 0.383 to cast the target casting 6 (see Figure 2).

[0075] After the casting 6 had cooled, a chipping pressure of 0.3 MPa was applied to one location on the casting 6 (indicated by the white arrow in Figure 2) using an air hammer for 3 seconds. This process was repeated 10 times to discharge sand from the casting's outlet (diameter: 16 mm). The total mass of the discharged sand was measured and divided by the total mass when all the sand was discharged, and the result was expressed as a percentage. A higher percentage indicates better disintegration properties.

[0076] - Adjustment of fire-resistant aggregate - First, as one of the refractory aggregates used in the examples and comparative examples, natural silica sand from Australia (product name: Flattery Sand) was prepared. Another refractory aggregate, recycled sand, was obtained by recovering silica sand from the casting process, subjecting it to magnetic separation, eddy current separation, and roasting treatments according to conventional methods, and then polishing the resulting recycled sand.

[0077] In each example and comparative example, the recycled sand and new sand prepared as described above were used as a mixed sand in a predetermined ratio, or as individual sands. The refractory aggregates (mixed sands) in the examples and comparative examples were all obtained by sieving using sieves that provide the respective AFS index, and the SiO2 content in each aggregate was measured by X-ray fluorescence analysis. Furthermore, the packing efficiency was determined by the measurement method described in the main text of the specification, as described above. In addition, the refractory aggregates consisting of mixed sand of recycled sand and new sand used in Examples 1 to 25 all had a shape factor of 1.40 or less, a surface adhesion viscosity content of 0.20% or less, and a hydrochloric acid soluble content of 3% or less, as measured by the above measurement method.

[0078] -Manufacturing of phenolic resin A- In a reaction vessel equipped with a thermometer, a stirrer, and a condenser, 940 parts of phenol, 440 parts of 47% formalin, and 2.8 parts of oxalic acid were added, respectively. Then, under stirring, the temperature inside the reaction vessel was gradually raised to the reflux temperature, and the reaction was carried out under reflux for 90 minutes. Furthermore, the reaction solution was heated and concentrated under reduced pressure until the temperature reached 170°C, thereby obtaining a solid phenolic resin A, which is a novolac-type phenolic resin with a weight-average molecular weight (Mw) of 1800, a softening point of 86°C, and containing 0.5% free phenol.

[0079] -Manufacturing of phenolic resin B- In a reaction vessel equipped with a thermometer, a stirrer, and a condenser, 188 parts of phenol, 1824 parts of bisphenol A, 428 parts of 47% formalin, and 2.8 parts of oxalic acid were added, respectively. Then, under stirring, the temperature inside the reaction vessel was gradually raised to the reflux temperature, and the reaction was carried out under reflux for 90 minutes. Furthermore, the reaction solution was heated and concentrated under reduced pressure until the temperature reached 170°C, thereby obtaining a solid phenol resin B, which is a bisphenol A-modified novolac type phenol resin with a weight-average molecular weight (Mw) of 1700, a softening point of 92°C, and containing 0.8% free phenol.

[0080] -Manufacturing of phenolic resin C- In a reaction vessel equipped with a thermometer, a stirrer, and a condenser, 680 parts of phenol, 535 parts of 47% formalin, and 101 parts of hexamethylenetetramine were charged. The mixture was heated to 70°C over approximately 60 minutes and allowed to react for 5 hours. Subsequently, the reaction mixture was heated to 90°C while under reduced pressure and dehydration. Then, 35 parts of ethylenebisstearamide were added to obtain phenol resin C, a solid ammonia resol type phenol resin with a weight-average molecular weight (Mw) of 2400 and a free phenol content of 4.5% by weight.

[0081] -Manufacturing of Phenolic Resin D- In a reaction vessel equipped with a thermometer, a stirrer, and a condenser, 940 parts of phenol, 1280 parts of 47% formalin, and 94 parts of a 50% caustic soda aqueous solution were added. The reaction vessel was then gradually heated under stirring and reacted at 80°C for 3 hours. Afterward, the mixture was concentrated under reduced pressure to obtain phenol resin D (60% resin solids), a liquid resol-type phenolic resin with a weight-average molecular weight (Mw) of 2200 and a free phenol content of 2.3% by weight. This liquid phenolic resin D also possesses water-retaining properties.

[0082] -Example 1- 100 parts of a mixed sand consisting of 50% recycled sand and 50% new sand was heated to 130-150°C in a sand heater. Then, 1.5 parts of a resin binder consisting of 75% phenol resin A and 25% liquid phenol resin D were added and mixed in a speed mixer for about 50 seconds. Then, an aqueous solution of hexamethylenetetramine, used as a hardening agent, was added in cooling water at a ratio of 3.0% relative to the resin solids in the resin binder. The mixture was kneaded until the sand separated into individual particles. Finally, 0.1 parts of calcium stearate was added and mixed for 15 seconds, after which the mixture was discharged from the mixer to obtain the desired dry RCS with fluidity at room temperature.

[0083] -Examples 2 to 25- Except for using a mixed sand consisting of recycled sand and new sand in the proportions shown in Tables 1 to 3 below as the refractory aggregate, and for incorporating the amount of hardener used, the composition and proportion of phenolic resin constituting the resin binder, and the proportions of the specified water-retaining agent, disintegration enhancer, good heat conductor, and additional vaporizing component, the same procedure as in Example 1 was followed to produce the desired dry RCS. The addition or blending of the water-retaining agent, disintegration enhancer, and good heat conductor was carried out together with the blending of the resin binder, and the additional vaporizing component was added and mixed in the hardener aqueous solution and carried out simultaneously with the addition of the hardener aqueous solution. Hereinafter, PEG used as the water-retaining agent represents polyethylene glycol, and PPG represents polypropylene glycol.

[0084] [Table 1]

[0085] [Table 2]

[0086] [Table 3]

[0087] -Comparative Example 1 to Comparative Example 8- Various RCSs were manufactured in the same manner as in Example 1, except that a mixed sand with the composition shown in Table 4 below was used as the refractory aggregate, and the proportions of the water-retaining agent, disintegration enhancer, and additional vaporizing component were set to those shown in Table 4 below, in addition to the amount of hardener used and the composition of the resin binder. The water-retaining agent and disintegration enhancer were kneaded together with the resin binder into the preheated refractory aggregate, while the additional vaporizing component was added after being mixed into the aqueous solution of the hardener.

[0088] [Table 4]

[0089] -RCS evaluation- In Examples 1 to 25 and Comparative Examples 1 to 8 described above, the vaporized component content, clump content, and mold characteristics (mold strength and hardening rate) after molding and secondary firing were evaluated for each of the various RCS produced. Casting tests were also conducted on the aluminum alloy molds obtained from these RCS to evaluate their collapse properties, and the results are shown in Tables 5 to 8 below.

[0090] [Table 5]

[0091] [Table 6]

[0092] [Table 7]

[0093] [Table 8]

[0094] As is clear from the results in Tables 5 to 7, each RCS obtained in Examples 1 to 25 used SiO2-based refractory particles with a filling rate of 53% or more as refractory aggregate, and the content of vaporized components mainly consisting of water was in the range of 300 to 2000 ppm, and the thermal conductivity of the RCS was 0.30 W / m·K or higher. As a result, the collapse of the mold after casting proceeded immediately when vibration was applied with an air hammer, and it was observed that the collapse properties were extremely good. In particular, the RCS obtained in Examples 6, 7, 10, 12 to 14 and 20 to 22 all showed extremely excellent results in terms of mold collapse properties due to the synergistic effect of the blending of collapse-improving agents.

[0095] In contrast, the RCS obtained in Comparative Examples 1 to 8, as shown in Table 8, used refractory particles with a high SiO2 content, but their packing density was low or their vapor content was low, resulting in insufficient thermal conductivity and poor mold properties. Furthermore, no effective mold collapse was observed in the mold collapse test, indicating that the RCS was inferior in terms of mold collapse resistance. [Explanation of symbols]

[0096] 2 Core test specimens 4 Outer mold 6 Castings

Claims

1. 50% by mass or more of SiO 2 The first step is to prepare a resin-coated sand which is made by kneading a refractory aggregate containing a certain substance and having a filling rate of 53% or more with a resin binder, and coating the surface of the refractory aggregate with the resin binder, and which contains a vaporized component having a boiling point of 300°C or less and a molecular weight of 100 or less in a ratio of 300 to 2000 ppm, and further having a thermal conductivity of 0.30 W / m·K or more, The second step involves filling the prepared resin-coated sand into a mold and forming the desired mold under heating. A third step involves performing a secondary firing treatment on the mold formed in the second step at a temperature of 200 to 300°C. A method for manufacturing a mold with excellent collapsibility, characterized in that, in the first step, a dry resin-coated sand having free flow at room temperature is prepared.

2. The aforementioned fire-resistant aggregate is silica sand and / or SiO 2 A method for manufacturing a mold with excellent collapsibility according to claim 1, characterized in that it mainly uses high-quality artificial aggregate.

3. The method for manufacturing a mold with excellent collapse properties according to claim 1 or 2, characterized in that the refractory aggregate has an AFS index of 30 to 90.

4. A method for producing a mold with excellent collapsibility according to any one of claims 1 to 3, characterized in that the resin binder mainly consists of a phenolic resin.

5. A method for producing a mold with excellent collapse properties according to any one of claims 1 to 4, characterized in that the vaporized component is liquid at 50°C.

6. A method for producing a mold with excellent disintegration properties according to any one of claims 1 to 5, characterized in that the vaporized component contains at least one of water, methanol, and phenol.

7. A method for producing a mold with excellent collapsibility according to any one of claims 1 to 6, characterized in that a water-retaining agent is further contained in the resin-coated sand.

8. A method for producing a mold with excellent disintegration properties according to any one of claims 1 to 7, characterized in that a disintegration enhancer is further contained in the resin-coated sand.

9. A method for manufacturing a mold with excellent collapse properties according to any one of claims 1 to 8, characterized in that a good thermal conductor is further contained in the resin-coated sand.

10. A method for manufacturing a mold with excellent collapsibility according to any one of claims 1 to 9, characterized in that at least a portion of the refractory aggregate is composed of refractory particles having a shape factor of 1.40 or less, a surface-adhering clay content of 0.20% by mass or less, and a hydrochloric acid-soluble content of 3% by mass or less.

11. The method for manufacturing a mold with excellent collapsibility according to claim 10, characterized in that the refractory particles are recycled from recovered sand collected in the casting process.

12. A method for manufacturing a mold with excellent collapsibility according to any one of claims 1 to 11, characterized in that a secondary firing process in the third step is performed on the mold that has been removed from the molding die.

13. A method for manufacturing a mold with excellent collapsibility according to any one of claims 1 to 12, characterized in that the hardening rate of the mold formed in the second step is 30% or more, and the hardening rate of such mold is further increased by the secondary firing treatment in the third step.

14. A method for manufacturing a mold with excellent collapsibility according to any one of claims 1 to 13, characterized in that the mold used in the second step is preheated to a temperature of 150 to 300°C.

15. A method for manufacturing a mold with excellent collapse properties, as described in any one of claims 1 to 14, characterized in that it is used for shaping a mold for casting molten aluminum alloy.

Citation Information

Patent Citations

  • Molding material for shell mold

    JP1987124046A

  • Fuel injection valve

    JP1993079423A

  • Molding material for shell mold

    JP1997001285A

  • Method and device for removing main mold and core for casting

    JP1997182952A

  • Method for recycling waste sand of green sand mold, and aggregate for mold

    JP2006068815A